THE EXPLOITS OF UZBEK SOLDIERS IN THE BATLLE OF STALINGRAD (BASED ON LETTERS FROM THE FRONT) (American Journal of Interdisciplinary Research and Development, 2023)
The National Archives of Uzbekistan contains a significant number of archival documents from the Second World War. The study of the Second World War is one of the topical scientific areas of Uzbek historical science. This interest is due to the fact that today, in the context of the revision and qualitative improvement of the system of international relations, this period of history is being carefully studied and objectively reassessed on the territory of almost all a former Soviet republics. The article describes the heroic exploits of Uzbek soldiers in the Battle of Stalingrad on the basis of letters from the front.